Shoot‐level flammability across the Dracophyllum (Ericaceae) phylogeny: evidence for flammability being an emergent property in a land with little fire. Issue 1 (11th June 2020) - Cui, Xinglei; Paterson, Adrian M.; Alam, Md Azharul; Wyse, Sarah V.; Marshall, Kate; Perry, George L. W.; Curran, Timothy J.
Summary: Plant flammability varies across species, but the evolutionary basis for this variation is not well understood. Phylogenetic analysis of interspecific variation in flammability can provide insights into the evolution of plant flammability. We measured four components of flammability (ignitability, sustainability, combustibility and consumability) to assess the shoot‐level flammability of 21 species of Dracophyllum (Ericaceae). Using a macroevolutionary approach, we explored phylogenetic patterns of variation in shoot‐level flammability. Shoot‐level flammability varied widely in Dracophyllum . Species in the subgenus Oreothamnus had higher flammability and smaller leaves than those in the subgenus Dracophyllum . Shoot flammability (ignitability, combustibility and consumability) and leaf length showed phylogenetic conservatism across genus Dracophyllum, but exhibited lability among some closely related species, such as D. menziesii and D. fiordense . Shoot flammability of Dracophyllum species was negatively correlated with leaf length and shoot moisture content, but had no relationship with the geographic distribution of Dracophyllum species. Shoot‐level flammability varied widely in the genus Dracophyllum, but showed phylogenetic conservatism. The higher flammability of the subgenus Oreothamnus may be an incidental or emergent property as a result of the evolution of flammability‐related traits, such as smaller leaves, which were selected for other functions and incidentally changed flammability.